Gamification of event tourism: unpacking the psychological mechanisms of gameful experience and engagement - Sesliokuyucu, Osman Seraceddin; Ali, Faizan; Sener, Gokhan; Cobanoglu, Cihan; Sayar, Gokcen (EMERALD GROUP PUBLISHING LTD, 2026)
PurposeThis study aims to investigate how specific gameful elements - enjoyment, absorption, creative thinking, activation, dominance and absence of negative affect - shape attendees' perceptions of hedonic and utilitarian values and their subsequent engagement in event tourism contexts.Design/methodology/approachGuided by the stimulus-organism-response (SOR) framework, a quantitative survey was conducted with 375 respondents via Amazon Mechanical Turk (MTurk). Participants with previous experience attending gamified events completed validated scales assessing gameful experiences, perceived values and engagement. Partial least squares path modeling (PLS-PM) was used to test the hypothesized relationships.FindingsThe analysis indicates that gameful experience increases both hedonic and utilitarian values, which subsequently enhance attendee engagement. The utilitarian pathway is stronger than the hedonic pathway, implying that functional benefits may play a salient role in sustaining engagement in event tourism. At the dimension level, enjoyment and dominance show the strongest effects. Overall, the results clarify how gameful design translates into deeper involvement through value-based psychological mechanisms.Research limitations/implicationsAlthough the study offers empirical insights into the cognitive and emotional pathways of gamification in event tourism, it relies on self-reported data from a single online panel and may not fully capture long-term behavioral outcomes. Future research should explore longitudinal effects and diverse event contexts.Practical implicationsEvent organizers and tourism marketers can strategically use gameful design to enrich both emotional satisfaction and functional value for attendees, thereby boosting engagement and enhancing the memorability of events. Moreover, integrating gameful elements into event tourism can foster more interactive, enjoyable and inclusive experiences that encourage community participation and emotional connection among diverse audiences.Social implicationsIntegrating gameful elements into event tourism supports more interactive, enjoyable and inclusive experiences, fostering community participation and emotional connection among diverse audiences.Originality/valueThis study advances SOR-based theorizing on gamified event tourism by explaining, in live physical event settings, how gameful experience translates into engagement through dual-value pathways (hedonic and utilitarian). By revealing an asymmetric pattern in which utilitarian value is more strongly related to engagement than hedonic value, the study refines when and why functional benefits can dominate engagement formation in contemporary event experiences. (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic):(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)--(sic)(sic),(sic)(sic),(sic)(sic)(sic)(sic)(sic),(sic)(sic),(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)--(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic)(sic)(sic)/(sic)(sic)/(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)-(sic)(sic)-(sic)(sic)(SOR)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic) Amazon Mechanical Turk(MTurk)(sic)(sic) 375 (sic)(sic)(sic)(sic)(sic).(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic),(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic) (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(PLS-PM)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic)(sic)(sic)/(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic),(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic)(sic)/(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)SOR(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic).(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic), (sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic)(sic). Gamificaci & oacute;n del turismo de eventos: an & aacute;lisis de los mecanismos psicol & oacute;gicos de la experiencia l & uacute;dica y la participaci & oacute;n de los asistentesResumenObjetivoEl presente estudio tiene como objetivo investigar c & oacute;mo determinados elementos l & uacute;dicos, diversi & oacute;n, absorci & oacute;n, pensamiento creativo, activaci & oacute;n, dominio y ausencia de afectos negativos, influyen en la percepci & oacute;n que tienen los asistentes del valor hed & oacute;nico y utilitario y en su posterior implicaci & oacute;n en contextos de turismo de eventos.Dise & ntilde;o/metodolog & iacute;a/enfoqueGuiados por el marco de est & iacute;mulo-organismo-respuesta (SOR), se realiz & oacute; una encuesta cuantitativa a 375 participantes a trav & eacute;s de Amazon Mechanical Turk (MTurk). Los participantes con experiencia previa en eventos gamificados completaron escalas validadas que evaluaban las experiencias l & uacute;dicas, los valores percibidos y la participaci & oacute;n. Se emple & oacute; el modelo de m & iacute;nimos cuadrados parciales (PLS-PM) para comprobar las relaciones hipot & eacute;ticas.ResultadosEl an & aacute;lisis indica que la experiencia l & uacute;dica aumenta tanto el valor hed & oacute;nico como el utilitario, lo que posteriormente mejora la participaci & oacute;n de los asistentes. La v & iacute;a utilitaria es m & aacute;s fuerte que la hed & oacute;nica, lo que implica que los beneficios funcionales pueden desempe & ntilde;ar un papel especialmente destacado en el mantenimiento de la participaci & oacute;n en el turismo de eventos. A nivel dimensional, el disfrute y el dominio muestran los efectos m & aacute;s fuertes. En general, los resultados aclaran c & oacute;mo la gamificaci & oacute;n promueve una mayor implicaci & oacute;n de los asistentes a trav & eacute;s de mecanismos psicol & oacute;gicos basados en el valor.Limitaciones/implicaciones de la investigaci & oacute;nAunque el estudio ofrece informaci & oacute;n emp & iacute;rica sobre las v & iacute;as cognitivas y emocionales de la gamificaci & oacute;n en el turismo de eventos, se basa en datos autoinformados de un & uacute;nico panel en l & iacute;nea y puede que no refleje completamente los resultados conductuales a largo plazo. Las investigaciones futuras deber & iacute;an explorar los efectos longitudinales y los diversos contextos de los eventos.Implicaciones pr & aacute;cticasLos organizadores de eventos y los profesionales del marketing tur & iacute;stico pueden emplear estrat & eacute;gicamente experiencias gamificadas para enriquecer tanto la satisfacci & oacute;n emocional (valor h & eacute;donico) como el valor funcional (valor utilitario) de los asistentes, lo que aumenta el compromiso y mejora la memorabilidad de los eventos. Adem & aacute;s, la integraci & oacute;n de elementos l & uacute;dicos en el turismo de eventos puede fomentar experiencias m & aacute;s interactivas, agradables e inclusivas que estimulen la participaci & oacute;n de la comunidad y la conexi & oacute;n emocional entre p & uacute;blicos diversos.Originalidad/valorEste estudio avanza en la teorizaci & oacute;n basada en la SOR sobre el turismo de eventos gamificado al explicar, en entornos de eventos f & iacute;sicos en vivo, c & oacute;mo la experiencia l & uacute;dica se traduce en compromiso a trav & eacute;s de v & iacute;as de valor duales (hed & oacute;nicas y utilitarias). Al revelar un patr & oacute;n asim & eacute;trico en el que el valor utilitario est & aacute; m & aacute;s relacionado con el compromiso que el valor hed & oacute;nico, el estudio aclara cu & aacute;ndo y por qu & eacute; los beneficios funcionales pueden dominar la formaci & oacute;n del compromiso en las experiencias de eventos contempor & aacute;neos.
Keywords: Event tourism; Gameful experience; Hedonic value; Utilitarian value; Engagement; (sic)(sic)(sic)(sic); (sic)(sic)(sic)(sic)(sic); Turismo de eventos; Experiencia l & uacute; dica; Valor hed & oacute; nico; Valor utilitario; Compromiso; CUSTOMER ENGAGEMENT; SCALE DEVELOPMENT; BRAND ENGAGEMENT; USER ENGAGEMENT; SERIOUS GAMES; CO-CREATION; UTILITARIAN; CONSUMPTION; IMPACT; Social Sciences - Other Topics